Some rules to transform sequence diagrams into coloured Petri nets - Ribeiro, Óscar Rafael Silva Ferreira (2006)
This paper presents a set of rules that allows software engineers to transform the behavior described by a UML 2.0 Sequence Diagram (SD) into a Colored Petri Net (CPN). SDs in UML 2.0 are much richer than in UML 1.x, namely by allowing several traces to be combined in a unique diagram, using high-level operators over interactions. The main purpose of the transformation is to allow the development team to construct animations based on the CPN that can be shown to the users or the clients in order to reproduce the expected scenarios and thus validate them. Thus, non-technical stakeholders are able to discuss and validate the captured requirements. The usage of animation is an important topic in this context, since it permits the user to discuss the system behavior using the problem domain language. A small control application from industry is used to show the applicability of the suggested rules.